Ratooning Ability & Performance of Hybrid Variety Mestizo7 (NSIC Rc136H), for Yield Characters under Different NPK Levels at Irrigated Low Land Conditions of Rice: Performance of Hybrid rice varieties for yield characters under different levels of NPK - Junejo, Ghulam Shabir; Tamayo, N.V.; Jarwar, Allah Dino; Jogi, Qamaruddin; Hullio, Muhammad Haroon; Junejo, Ghulam Qadeer; Kaleri, Rameez Raja (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Field experiments were used in experimental research sites from Centeral Luzon State University (CLSU), Science city of Munoz Nueva Ecija, Philippines, to value the level of nitrogen in hybrid variety Mestizo7 Hybrid (NSIC Rc136 H) was used as observation matter material. In the characters of performance. Mestizo7 was more spikelets / panicles, full grain and grain production / ha. To determine the ratoon crop as issue of fertilizer, level of hybrid variety Mestizo7 at 120-30-30 kg NPK / ha, 4768 for the longest crop. The 00 kg / ha and 150-30-30 kg / kg NPK / kg 4714 kg/ha, was the production of grain production, 100 percent. Production increased by 33 percent and 99.20% of non-nutrition plants with 2380 kg / ha.